Inhibition of macrophages inflammasome activation via autophagic degradation of HMGB1 by EGCG ameliorates HBV-induced liver injury and fibrosis - He, Minjing; Chu, Tianhao; Wang, Ziteng; Feng, Ying; Shi, Runhan; He, Muyang; Feng, Siheng; Lu, Lin; Cai, Chen; Fang, Fang; Zhang, Xuemin; Liu, Yi; et al. (Frontiers in Immunology, 2023)
Background Liver fibrosis is a reversible wound-healing response that can lead to end-stage liver diseases without effective treatment, in which HBV infection is a major cause. However, the underlying mechanisms for the development of HBV-induced fibrosis remains elusive, and efficacious therapies for this disease are still lacking. In present investigation, we investigated the effect and mechanism of green tea polyphenol epigallocatechin-3-gallate (EGCG) on HBV-induced liver injury and fibrosis. Methods The effect of EGCG on liver fibrosis was examined in a recombinant cccDNA (rcccDNA) chronic HBV mouse model by immunohistochemical staining, Sirius red and Masson’s trichrome staining. The functional relevance between high mobility group box 1 (HMGB1) and inflammasome activation and the role of EGCG in it were analyzed by Western blotting. The effect of EGCG on autophagic flux was determined by Western blotting and flow cytometric analysis. Results EGCG treatment efficiently was found to alleviate HBV-induced liver injury and fibrosis in a recombinant cccDNA (rcccDNA) chronic HBV mouse model, a proven suitable research platform for HBV-induced fibrosis. Mechanistically, EGCG was revealed to repress the activation of macrophage NLRP3 inflammasome, a critical trigger of HBV-induced liver fibrosis. Further study revealed that EGCG suppressed macrophage inflammasome through downregulating the level of extracellular HMGB1. Furthermore, our data demonstrated that EGCG treatment downregulated the levels of extracellular HMGB1 through activating autophagic degradation of cytoplasmic HMGB1 in hepatocytes. Accordingly, autophagy blockade was revealed to significantly reverse EGCG-mediated inhibition on extracellular HMGB1-activated macrophage inflammasome and thus suppress the therapeutic effect of EGCG on HBV-induced liver injury and fibrosis. Conclusion EGCG ameliorates HBV-induced liver injury and fibrosis via autophagic degradation of cytoplasmic HMGB1 and the subsequent suppression of macrophage inflammasome activation. These data provided a new pathogenic mechanism for HBV-induced liver fibrosis involving the extracellular HMGB1-mediated macrophage inflammasome activation, and also suggested EGCG administration as a promising therapeutic strategy for this disease.